Efektifitas Media Paper Plate Terhadap Kecerdasan Naturalis Bagi Anak Usia Dini - Dinda Nur Akmalia; Rina Syafrida; Ine Nirmala (Peneliti.net, 2022)
Education is an activity to develop human potential in the learning process of life. This learning is done so that humans can develop with their respective abilities. In addition to aspects of child development, there is also a type of intelligence in children. One of these intelligences is naturalist intelligence, this relates to the intelligence of children who are dominant or prefer to observe, explore, and learn things around them. Naturalist intelligence is important to be stimulated in early childhood. There are so many media that exist to develop children's naturalist potential, one of which is paper plate. Based on the hypothesis test, the results of the pretest and posttest were obtained in group B of Rumah Pelangi Islamic Kindergarten. The following are the results of the pretest and posttest t-test for group B of Rumah Pelangi Islamic Kindergarten. In this study, the results obtained tcount > ttable (31.313 > 2,120) thus Ho is rejected and Ha is accepted which means that there is an average difference between pretest and posttest so it can be concluded that there is a significant effectiveness in the use of paper plate media on naturalist intelligence of children aged early.